The Relationship Between Physical Activity and Emotional Intelligence in College Students: The Mediating Role of Self-Efficacy - Wang, Kun; Yang, Ying; Zhang, Tingran; Ouyang, Yiyi; Liu, Bin; Luo, Jiong (Frontiers in Psychology, 2020)
Background: College students are an inexhaustible driving force for social development, and college students with good physical and psychological qualities can better adapt to changes in the external environment. The purpose of this study was to explore the intrinsic relationship of physical activity and emotional intelligence among college students and to determine the primary role of self-efficacy in their relationships. Methods: Eight hundred thirty-five college students from two comprehensive universities in Southwest China, whose average age was 20.13 ± 1.06 years old, were investigated using the Physical Activity Rating Scale (PARS-3), Chinese Emotional Intelligence Scale (EIS), General Self-Efficacy Scale (GSES), and other measuring tools. SPSS 22.0 software was used to analyze and process the data with Independent sample t-test, One-way ANOVA, Pearson correlation analysis and regression analysis, and Amos 21.0 software used to build the structural equation model. Results: (1) In terms of physical activity amount, self-efficacy, and emotional intelligence, male college students scored higher than female students. Furthermore, college students in humanities and social sciences had lower self-efficacy. In contrast, senior students had the lowest levels of physical activity and self-efficacy, and there was no discipline or grade distribution difference in emotional intelligence. (2) Physical activity amount was positively correlated with emotional intelligence (r = 0.24, P < 0.001), physical activity amount was positively correlated with and self-efficacy (r = 0.26, P < 0.001), and self-efficacy was positively correlated with emotional intelligence in college students (r = 0.18, P < 0.001). (3) Self-efficacy played a partial mediating role between physical activity and emotional intelligence in college students (ES = 0.06). Conclusion: Regular physical activity can improve the self-efficacy and emotional intelligence of college students, and effectively promote the physical and mental development of students.